Risk factors for recurrent wheezing in infants - Lustosa, Wellyne Alves; Melo, Marta Lígia Vieira; De Andrade Isidório, Ubiraídys; De Sousa, Milena Nunes Alves; De Abreu, Luiz Carlos; Valenti, Vitor E. [UNESP]; Cardoso, Marco A. [UNESP]; De Assis, Elisangela Vilar (My University, 2013)
Introduction: wheezing is one of the most common respiratory symptoms in childhood. Regardless of the cause, it is a reason to seek medical care in emergency rooms, especially if there is recurrence of episodes. Very common in childhood, recurrent wheezing has its first episodes in the first year of life. We sought to examine the risk factors for recurrent wheezing in infants in the first year of life. Methods: this is a cross-sectional quantitative study in which a standardized questionnaire of the International Study of Wheezing in Infants, translated and validated in Brazil, consisting of objective questions, applied 40 mothers were enrolled in two Family Health units. Results: the risk factors found were: smoking during pregnancy, family history of asthma, rhinitis and allergic dermatitis, the presence of at least one pet in the home at the time of birth and age at first cold less than or equal to three months of life. No significant relationships were found between males and wheezing, exclusive breastfeeding or numbers of colds in the first year of life. Conclusion: our findings are different from those reported in the literature.
Keywords: Infants; Respiratory sounds; Risk factors; wheezing